Wells Fargo project gets underway (Raton, NM Raton Range, 1996)
Article is about renovations to be done on the new location for the Old Pass Gallery and Art and Humanities Council's offices.
Newspaper Article + 2 Photographs 1)Joe Apache, Dave Little, Barbara Carlini, Monte Coangelo, Melissa Goetsch-Medina, Frank Main, Eric Honeyfield and Bill Fegan. 2)Joe Apache, Barbara Carlini, Bill Fegan, and Melissa Goetsch-Medina.
Master list item #: 63
File location is in the Raton file Cabinet
Keywords: Apache, Joe -- City of Raton Mayor; Little, Dave -- Architect; Carlini, Barbara -- Art and Humanities Council Executive Director; Colangelo, Monte -- Colangelo Builders; Goetsch-Medina, Melissa -- Old Pass Gallery Director; Main, Frank -- City of Raton Engineer; Honeyfield, Eric -- City of Raton Manager; Fegan, Bill; Old Pass Gallery; Wells Fargo; Art and Humanities Council; New Mexico State Highway and Transportation Department; Building Renovations; ISTEA Grant; Raton, New Mexico